1998
DOI: 10.1099/00222615-47-5-391
|View full text |Cite
|
Sign up to set email alerts
|

Clostridial pathogenicity in experimental necrotising enterocolitis in gnotobiotic quails and protective role of bifidobacteria

Abstract: The pathogenesis of neonatal necrotising enterocolitis (NEC) remains unclear. Gnotobiotic quails fed a lactose diet have been used to investigate the role of clostridial strains originating from faecal specimens of neonates through the intestinal lesions, the changes in microflora balance and the production of bacterial metabolites, i.e., shortchain fatty acids and hydrogen. Bifidobacteria are thought to exert various beneficial effects on host health, including interaction with the colonic microflora. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 59 publications
6
131
1
2
Order By: Relevance
“…Butyrate has been shown to increase mucosal injury by enhancing the production of stromelysin-1 in cytokine-stimulated gut mesenchymal cells (169) . Generally, high levels of clostridia have been linked with the production of butyric acid, while bifidobacteria, by causing a decrease in clostridia numbers, have been associated with a decrease or disappearance of butyric acid (170) . Furthermore, it has been reported that the application of probiotic bifidobacteria reduced both the incidence and severity of NEC in premature neonates (171,172) .…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…Butyrate has been shown to increase mucosal injury by enhancing the production of stromelysin-1 in cytokine-stimulated gut mesenchymal cells (169) . Generally, high levels of clostridia have been linked with the production of butyric acid, while bifidobacteria, by causing a decrease in clostridia numbers, have been associated with a decrease or disappearance of butyric acid (170) . Furthermore, it has been reported that the application of probiotic bifidobacteria reduced both the incidence and severity of NEC in premature neonates (171,172) .…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…Intestinal mucosal injury, bacterial coloni- sation, rapid increase in the gas volume of gastric aspirate and formula feeding are thought to be factors in the development of NEC (Butel et al 1998). Hence, it is rare in infants whose diet includes breast milk, being six to ten times more common in exclusively formula-fed infants (Dai & Walker, 1998).…”
Section: Neonatal Necrotising Enterocolitismentioning
confidence: 99%
“…Animal models of NEC have implicated Clostridium spp. Studies carried out by Butel et al (1998) examined the possible role of C. butyricum as the pathological agent of NEC. Germ-free quails were used as experimental models and were fed on a semi-synthetic diet containing 8 % lactose.…”
Section: Neonatal Necrotising Enterocolitismentioning
confidence: 99%
“…Lesions occurred rapidly after inoculation with the necrotising enterocolitis flora (thickening of the caecal wall with gas cysts, haemorrhagic ulcerations, and necrotic areas), whereas they did not in the presence of B. infantis and B. longum. Colonisation with bifidobacteria suppressed the growth of C. butyricum and led to the complete disappearance of C. perfingens (Butel et al 1998). Additional effects of supplementation with oligofructose upon those seen with bifidobacteria alone were demonstrated in subsequent investigations in similar models.…”
Section: Data From Animal Studiesmentioning
confidence: 80%